Profit and Loss Sharing Berdasarkan Konsep Al-Falah Dalam Meningkatkan Kesejahteraan Pada Bisnis Syirkah: (Studi Pada Saunk Coffe and Resto) - marzuka, syafika; Muchlis, Mustakim; Jannah, Raodahtul (ISAFIR: Islamic Accounting and Finance Review, 2025)
The development of debt-free businesses is attracting more and more attention. One model is the shirkah business. In shirkah, the investor and business manager work together with a profit-sharing system agreed upon from the start. However, in practice, many business actors have not fully implemented Islamic principles. This study aims to examine the profit sharing calculation system, the application of dividend tax, and the implementation of the Al-Falah concept in improving welfare through the syirkah model at Saunk Coffee and Resto. The research method used is descriptive qualitative, with primary and secondary data. The results showed that the profit-sharing system applied by Saunk Coffee and Resto was not fully in accordance with the initial contract. However, as long as both parties agree with each other, the contract is still considered sharia-compliant. The tax on dividends has not been applied because it is influenced by behavior and a business environment that is not yet supportive.